Artificial Intelligence in Coronary CT Angiography: Current Status and Future Prospects - Liao, Jiahui; Huang, Lanfang; Qu, Meizi; Chen, Binghui; Wang, Guojie (Frontiers in Cardiovascular Medicine, 2022)
Coronary heart disease (CHD) is the leading cause of mortality in the world. Early detection and treatment of CHD are crucial. Currently, coronary CT angiography (CCTA) has been the prior choice for CHD screening and diagnosis, but it cannot meet the clinical needs in terms of examination quality, the accuracy of reporting, and the accuracy of prognosis analysis. In recent years, artificial intelligence (AI) has developed rapidly in the field of medicine; it played a key role in auxiliary diagnosis, disease mechanism analysis, and prognosis assessment, including a series of studies related to CHD. In this article, the application and research status of AI in CCTA were summarized and the prospects of this field were also described.